Analisis komprehensif peran ehealth dalam model bisnis pelayanan kesehatan modern: Tinjauan sistematis literatur - Putri, Adhisa Restu; Sukamto, Sukamto (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The integration of eHealth technologies supports this shift by improving data management, patient engagement, and real-time communication between stakeholders. Healthcare organizations are increasingly adopting digital tools to simplify operations, reduce costs, and improve clinical outcomes. Furthermore, eHealth solutions facilitate prevention and chronic disease management, which align with the long-term sustainability goals of healthcare systems. The flexibility of eHealth also supports remote services and personalized care, which are core to emerging business strategies. Purpose: To assess the strategic role of eHealth in the transformation of modern healthcare business models. Method: The literature review used PubMed, Cochrane Library, and Google Scholar databases with the keywords